Efektivitas Kebijakan Harga Input dan Output Usahatani Tanaman Pangan pada Berbagai Agroekosistem di Indonesia - Andriati, Andriati; Sudana, Wayan (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Fertilizers play important roles in increasing rice yield. Government policy in a form of determined Highest Retail Price (HRP) of urea and the Government Purchasing Price (GPP) of rice grains not always been effective, so that farmers might not rationally use the fertilizers. Assessment the effectiveness of policy on the implementation HRP and GPP was conducted in five provinces, with different agro-ecosystem. The assessment used primary data collected in 2008, with aim to analyze the effectiveness of the policy implementation on urea HRP and on rice grains GPP. Assessment locations at the provincial and regency levels were determined based on a purposive sampling technique, whereas assessment locations at the district to village levels were selected based on the production center, determined by the multistages random sampling. Data collection of input and output prices were done through surveys using structured questionnaires to kiosks of farm inputs at the village level, the Village Cooperative Units (KUD), and other relevant agencies. Results of the assessments indicated that policy on HRP of urea fertilizer was not effectively complied, especially in the irrigated land with a high-low tidal agro-ecosystem. The GPP policy implementation was quite effective; in the aggregate, the most effective implementation of the policy was on the irrigated lands. The highest level of farmers’ ability to buy urea fertilizer (IHKD) was on the irrigated land. The urea HRP policy is expected to go along with the increase of grain GPP.